Histiocytic Sarcoma with an Unusual Clinical Manifestation Imitating Malignant Vascular Tumor: A Case Report - Ondruššek, Róbert; Žmolíková, Jana; Šimová, Jarmila; Bartová, Petra; Hurník, Pavel; Uvírová, Magdalena; Žiak, Dušan (The American journal of case reports, 2022)
BACKGROUND Histiocytic sarcoma is a rare malignant hematopoietic neoplasm with morphologic and immunohistochemical features of histiocytic differentiation, usually with unfavorable prognosis. Despite aggressive biological behavior, in subgroup of patients with localized disease, the prognosis can be very good. Few publications are available on localized cases of histiocytic sarcoma. These occur infrequently and continue to be a poorly-recognized morphological entity. CASE REPORT A 73-year old man treated for Parkinson syndrome presented with a tumor resistance on the dorsal surface of the left forearm. This lesion was clinically seen as an organized hematoma and was surgically resected. Histologically, the tumor was situated in the dermis and subcutis and it consisted of multiple neoplastic nodules. Vasoformative growth patterns with the vascular-like spaces containing erythrocytes and hemosiderin pigment presence simulated the morphology of angiosarcoma. Based on the immunohistochemical characteristics, we diagnosed the tumor as cutaneous histiocytic sarcoma. Genetic analysis revealed immunoglobulin heavy-chain gene rearrangement without any concomitant hematological malignancy. The patient demonstrated no systemic disease or impairment associated with diagnosed histiocytic sarcoma, and no recurrence has been found to date. CONCLUSIONS We report a case of primary cutaneous histiocytic sarcoma with an excellent outcome after surgical treatment only. Clinical data and histopathological and immunohistochemical evaluation were essential to rule out other malignant tumors in the differential diagnosis. Genetic analysis together with up-to-date knowledge and understanding of principles of tumorous transformations helped to diagnose this poorly-recognized entity with various clinical behaviors.
Keywords: histiocytární sarkom; nádory kůže; Diagnosis, Differential; lidé; Histiocytic Sarcoma; Vascular Neoplasms; Aged; Humans; Skin Neoplasms; senioři; diferenciální diagnóza; mužské pohlaví; vaskulární nádory; Male